DNA Methylation Profiling in a Neuroblastoma Cell Line Exposed to the Antipsychotic Perospirone - Murata, Yui; Bundo, Miki; Sunaga, Fumiko; Kasai, Kiyoto; Iwamoto, Kazuya (Pharmacopsychiatry, 2019)
Introduction Accumulating evidence suggests the importance of epigenetic changes in the brain induced by antipsychotic drugs. However, due to the lack of systematic investigation, their effects on epigenetic status remain largely unclear. During the course of examining the epigenetic effects of antipsychotics, we here focused on perospirone, an atypical antipsychotic drug mainly used in Japan.Methods Genomic DNA was obtained from human neuroblastoma cells exposed to 2 different doses of perospirone. Comprehensive DNA methylation analysis was performed using the Infinium HumanMethylation450 BeadChip.Results Of about 470,000 probes, perospirone exposure changed DNA methylation at 4098 probes. These probes were enriched to genes for neural development. Probes showing hypermethylation were mainly found at gene body and intergenic regions, whereas those that showed hypomethylation were located near promoter regions. Additionally, DNA methylation changes were found in the probes for dopamine receptor 2 and serotonin receptor (HTR) 2A and HTR1A, which are the pharmacological targets of atypical antipsychotics.Discussion Our comprehensive DNA methylation analyses will contribute to a better understanding of detailed pharmacological actions of perospirone.
Keywords: epigenetics; antipsychotic drug; HumanMethylation450 BeadChip; SK-N-SH cell